Academic plagiarism in Malaysia higher education institutions: legal perspective - Mohamed, Khadijah; Abdul Samat, Nor Hayati; Abd Aziz, Ahmad Shamsul; Mohd Noor, Nor Azlina; Ismail, Norain (Global Academic Excellence, 2018)
The incidents of plagiarism are prevalent in the academic community throughout the world. In the context of the academic community, plagiarism may damage the reputation as well as negatively affect the credibility and integrity of the institutions and those involved in such behaviours. This paper provides an overview of academic plagiarism in Malaysia and discusses the relevant Malaysian legal provisions, specifically those which applied to Malaysian public higher education institutions concerning the issue of plagiarism. Analysis of statutes and relevant case law was done by employing the doctrinal legal method. It is learned that a number of statutes governing the management and administration of the universities in Malaysia contain provisions on plagiarism that are to be subjected to disciplinary punishment. Of all the statutes, the paper found that the Educational Institutions (Discipline) Act 1976 (Act 174), which governs matters related to discipline in educational institutions but not including universities explicitly stated provision on plagiarism. The paper suggests that universities should adopt clear policy or guideline on student writing handling in order to avoid and deal with plagiarism issues effectively.